2016
DOI: 10.18632/oncotarget.8720
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor one B (NFIB) encodes a subtype-specific tumour suppressor in glioblastoma

Abstract: Glioblastoma (GBM) is an essentially incurable and rapidly fatal cancer, with few markers predicting a favourable prognosis. Here we report that the transcription factor NFIB is associated with significantly improved survival in GBM. NFIB expression correlates inversely with astrocytoma grade and is lowest in mesenchymal GBM. Ectopic expression of NFIB in low-passage, patient-derived classical and mesenchymal subtype GBM cells inhibits tumourigenesis. Ectopic NFIB expression activated phospho-STAT3 signalling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 77 publications
3
41
2
Order By: Relevance
“…For example, it has been suggested that NFIA is involved in the neuroprotection of neurons following administration of sub‐lethal doses of N‐methyl‐D‐aspartate (Zheng et al, ) and inhibition of remyelination in human myelin disorders via regulation of oligodendrocyte progenitor differentiation (Fancy et al, ). NFI proteins have also been implicated in mental disorders, such as autism (Chuang et al, ; Tsang et al, ) and bipolar disorder (Le‐Niculescu et al, ), as well as multiple sclerosis (Fancy et al, ), Parkinson's disease (Suwarnalata et al, ), and brain tumours (Genovesi et al, ; Glasgow et al, ; Ho et al, ; Idbaih et al, ; Lacroix et al, ; Lastowska et al, ; Lee et al, ; Song et al, ; Stringer et al, ; Vyazunova et al, ). The NFI expression pattern in the adult cortex provides a basis for investigating their function in these diseases, and identifying the cell types involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been suggested that NFIA is involved in the neuroprotection of neurons following administration of sub‐lethal doses of N‐methyl‐D‐aspartate (Zheng et al, ) and inhibition of remyelination in human myelin disorders via regulation of oligodendrocyte progenitor differentiation (Fancy et al, ). NFI proteins have also been implicated in mental disorders, such as autism (Chuang et al, ; Tsang et al, ) and bipolar disorder (Le‐Niculescu et al, ), as well as multiple sclerosis (Fancy et al, ), Parkinson's disease (Suwarnalata et al, ), and brain tumours (Genovesi et al, ; Glasgow et al, ; Ho et al, ; Idbaih et al, ; Lacroix et al, ; Lastowska et al, ; Lee et al, ; Song et al, ; Stringer et al, ; Vyazunova et al, ). The NFI expression pattern in the adult cortex provides a basis for investigating their function in these diseases, and identifying the cell types involved.…”
Section: Discussionmentioning
confidence: 99%
“…The NFI expression pattern in the adult cortex provides a basis for investigating their function in these diseases, and identifying the cell types involved. For instance, NFIA (Glasgow et al, ; Lee et al, ; Song et al, ; Vyazunova et al, ) and NFIB (Idbaih et al, ; Stringer et al, ) are both associated with the progression of glioma, a brain cancer of astrocytic origin. Future studies using cell type‐specific and/or inducible deletion of NFI proteins will be required to delineate their precise role in these cell types in order to understand the full extent of their post‐developmental role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioblastoma can be molecularly classified into proneural, neural, classical, and mesenchymal types according to The Cancer Genome Atlas (TCGA) 36 . We use two glioblastoma cell models, T98G and U-251MG, which are both of caucasian male origin and classified as mesenchymal type with p53 mutant genotype 37,38 . The adhesion and electrotaxis of T98G and U-251MG glioblastoma cell lines on various ECMs are tested in a double-layer hybrid multiple electric field chip (HMEFC) based on the hybrid PMMA/PDMS design approach 17 (Supplementary TABLE. S.1).…”
Section: B Glioblastoma Electrotaxis Requires Optimal Laminin-contaimentioning
confidence: 99%
“…Both T98G cells and U-251MG cells are categorized as mesenchymal type glioblastoma 37,38 , however, their electrotactic responses are completely different. Similar results are reported in the electrotaxis of glioblastoma cells and spheroids 15,16,19,39 and lung adenocarcinoma 51 , showing that although molecular and surface marker makeups of the cell lines are similar, their electrotaxis responses can be completely different.…”
Section: Electrotaxis Behavior May Reflect the Heterogeneity Of Glmentioning
confidence: 99%